Total knee arthroplasty following previous hardware implantation: do hardware removal strategies influence periprosthetic joint infections? A systematic review and meta-analysis - Domenico De Mauro; Chiara Comisi; Enrico Festa; Tiziana Ascione; Massimo Mariconda; Giovanni Balato (EFORT Open Reviews)
Purpose: Total knee arthroplasty (TKA) in patients who underwent previous knee surgeries can be a challenging procedure both technically and for the complication rate. Conversion TKA is affected by a higher risk of infection compared to primary TKA. The aims of this meta-analysis are i) to compare the infectious risk among patients undergoing TKA after a prior hardware implantation, evaluating removal vs maintenance of the hardware, and ii) within the removal group, to compare staged vs concurrent procedure. Methods: In accordance with the PRISMA guidelines, a systematic literature review was conducted up to January 2024. The review was registered in the PROSPERO database: CRD42024510444. The inclusion criteria comprised the following: i) patients aged 18 years or older, ii) individuals who had undergone total knee replacement and iii) those with a history of prior nonabsorbable hardware implantation. The pooled incidence of periprosthetic joint infections (PJI) was reported using odds ratios with corresponding 95% confidence intervals (CIs). Results: The investigation of database and references identified 284 studies. PJI risks differed significantly among groups, with a higher risk in the removal group (z = 3.5630, P = 0.0004). Furthermore, within the removal group, the risk of PJI was lower in cases of staged removal compared to concurrent removal (z = 2.0931, P = 0.0363). Conclusions: TKA following a previous knee hardware implantation indicates a higher PJI risk when the hardware is removed compared to leaving it in place. If hardware removal is necessary, staged removal is recommended. The presence of minor hardware is the only scenario where, if removal is necessary, one-stage approach is preferred.